If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26x + -6 + -17x + 3 = 19x + -4 + -10x + 16 Reorder the terms: -6 + 3 + 26x + -17x = 19x + -4 + -10x + 16 Combine like terms: -6 + 3 = -3 -3 + 26x + -17x = 19x + -4 + -10x + 16 Combine like terms: 26x + -17x = 9x -3 + 9x = 19x + -4 + -10x + 16 Reorder the terms: -3 + 9x = -4 + 16 + 19x + -10x Combine like terms: -4 + 16 = 12 -3 + 9x = 12 + 19x + -10x Combine like terms: 19x + -10x = 9x -3 + 9x = 12 + 9x Add '-9x' to each side of the equation. -3 + 9x + -9x = 12 + 9x + -9x Combine like terms: 9x + -9x = 0 -3 + 0 = 12 + 9x + -9x -3 = 12 + 9x + -9x Combine like terms: 9x + -9x = 0 -3 = 12 + 0 -3 = 12 Solving -3 = 12 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| x+5-1=26-14 | | x^2+2=23 | | (11-2x)(6-2x)(x)=40 | | .04(x)+.08(x)=10000 | | x+(.07*x)=100 | | 4v^2+24v-64= | | .04(x)+.08(x)=-124 | | 6x+13-8x=16-15x+13x-3 | | -1/3y=-9 | | 50g-7=44g+35 | | x-4=2(3x-1) | | 12x=11x-14x | | x+(.07*x)=50 | | 2(3+2x)-3=27 | | .02(.8x)+.05x=119.6 | | sqrt(x-1)+x=7 | | 2.5+.075p=.01p | | 5ln(2x-2)+10=0 | | X^2+13x-31=7x-4 | | 20x+10=5*20 | | 2.1x-8.1=3.16-5.4x | | 2p^2/5-p^1/5-1=0 | | H(t)=-10t^2+10t+24 | | .05x+.06(3x)=943 | | 5y-3+y+29=5y+30-1y | | .6n-.6=6n+1.3 | | 3x+20=8x-40 | | 6g+18=9g-25 | | -7-7(4x+8)=-175 | | a-a^1/2-6=0 | | 3x+20=4x-5 | | a-a^1/2-6= |